Class Management In Inclusive Mathematics Learning With Simple Media - Putra, Eric Dwi; Damayanti, Alfina; Agustin, Anissa Dwi; Oktavia, Dita; Maulida, Etik Puja; Djamali, Mochammad Fadil (Fakultas Ilmu Pendidikan (FIP) Universitas Hasyim Asy'ari (Unhasy) Tebuireng Jombang, 2026)
This research is motivated by the importance of classroom management in supporting successful mathematics learning, particularly in the context of inclusive education, which demands adjustments to learning strategies according to student characteristics. This study aims to describe the initial conditions of mathematics learning, the implementation of simple learning media, and their impact on student interaction and activeness. The approach used was descriptive qualitative with one mathematics teacher and three seventh-grade students in a junior high school as subjects. Data collection techniques included observation, interviews, and documentation, while data analysis was carried out through the stages of reduction, presentation, and drawing conclusions. The results showed that initial learning was still dominated by lecture methods with limited media, resulting in low student participation. The implementation of the number card media was proven to increase student engagement and interaction. Although students initially showed hesitation, they became more active and enthusiastic after becoming accustomed to using the media. These findings indicate that simple learning media can be an effective strategy to improve the quality of mathematics learning, especially in conditions of limited facilities and infrastructure.